ANALISIS FAKTOR YANG MEMPENGARUHI PENGELUARAN DI DAERAH TUJUAN, JUMLAH REMITAN PEDAGANG KAKI LIMA KECAMATAN MENGWI - Shidqy, Aufa Rafiv; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 12 (2023): Vol.12.No.12. DESEMBER 2023, 2023)
The purpose of this study was to analyze the direct effect of income, the number of dependents in the destination area, and the presence of nuclear family members in the area of origin on expenditure in the destination area and the amount of remittances, as well as the indirect effect through expenditure in the destination area of street vendors in Mengwi District. Location this research in Mengwi District, Badung Regency. Sample technique uses accidental sampling as 80 samples. Data analysis technique used path analysis with the SPSS program. Results are income has significant positive on expenditure in destination area and the amount remittances. Number of dependents and presence of nuclear family members in area of origin don’t have significant effect on expenditure in destination area. Number of dependents has a significant negative effect on the amount of remittances. Presence of nuclear family members did not significantly affect the amount of remittances. Expenditure in destination area has significant negative effect on the amount of remittances from street vendors in Mengwi District. Income has partial indirect effect on the amount of remittances through spending in the destination area. Meanwhile, the number of dependents in the destination area and the presence of nuclear family members are not. Keywords: Income, Number of Dependents, Existence of Nuclear Family Members, Expenditures, Remittances